The Effect of Inquiry Model on Science Learning Outcomes Reviewed from Self-Regulated Learning in Elementary School - Yuliawati, Ni Putu Feny; Suastika, I Nengah; Ardana, I Made (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The low results of science learning are one of the things that underlie this research. This study aims to determine the effect of the inquiry model on science learning outcomes in terms of students’ self-regulated learning. The type of research used in this study is a quasi-experimental design with a posttest-only control group design. The population of the study is all fifth-grade students of SDN Gugus II Gianyar, totaling 180 students. Sampling used a random sampling technique and obtained two classes, with total 65 students. Data collection used test and non-test methods. Data were analyzed using ANOVA AB analysis. The results of the study showed: 1) The science learning outcomes of students who were taught with the inquiry model were better than those of students who were taught with the conventional model; 2) There was an interactive effect between the inquiry model and self-regulated learning on science learning outcomes; 3) In students with high self-regulated learning, there was a difference in science learning outcomes between students who were taught with the inquiry model and students who were taught with the conventional model; 4) In students with low self-regulated learning, there was a difference in science learning outcomes between students who were taught using the inquiry model and students who were taught using the conventional model. Based on the findings obtained, it can be concluded that the inquiry model has an effect on the results of science learning in terms of students’ self-regulated learning.